Fabrication and characterization of zein/carboxymethyl chitosan nanoparticles for co-encapsulation of curcumin and resveratrol - Wang, Pan; Yin, Ying; Zhang, Yue; Shao, Jing (Frontiers in Nutrition, 2025)
IntroductionCurcumin and resveratrol are promising nutraceuticals, but their application in functional foods is limited by poor water solubility, low bioavailability, and chemical instability. This study aimed to develop a novel co-delivery system to overcome these challenges.MethodsCurcumin/resveratrol-zein-carboxymethyl chitosan (CRZC) nanocomplexes were fabricated using an antisolvent precipitation method. The mass ratio of zein to CMCS was optimized. The nanoparticles were characterized for size, encapsulation efficiency (EE), and antioxidant activity. Their stability during storage and simulated gastrointestinal digestion was also evaluated.ResultsThe optimized CRZC nanoparticles (zein:CMCS mass ratio of 2:1) exhibited a small particle size (201.6 nm), high encapsulation efficiency (72.90% for curcumin and 78.23% for resveratrol), and superior radical scavenging capacity. Structural characterization confirmed that hydrophobic interactions, electrostatic attraction, and hydrogen bonding were the main forces maintaining nanocomplex integrity. The CMCS coating significantly improved the storage and digestion stability of both encapsulated bioactives.DiscussionThese results demonstrate that the zein-CMCS-based nanocomplex is an efficient and robust delivery system. The CRZC nanoparticles show great potential for the co-delivery of synergistic nutraceuticals to enhance the functionality and application of bioactive compounds in the food industry.